Femoral neck trabecular bone: loss with aging and role in preventing fracture. - Thomas, C; Mayhew, P; Power, J; Poole, K; Loveridge, N; Clement, J; Burgoyne, C; Reeve, J (2009)
Hip fracture risk rises 100- to 1000-fold over six decades of age, but only a minor part of this increase is explained by declining BMD. A potentially independent cause of fragility is cortical thinning predisposing to local crushing, in which bone tissue's material disintegrates at the microscopic level when compressed beyond its capacity to maintain integrity. Elastic instability or buckling of a much thinned cortex might alternatively occur under compression. In a buckle, the cortex moves approximately at right angles to the direction of load, thereby distorting its microstructure, eventually to the point of disintegration. By resisting buckling movement, trabecular buttressing would protect the femoral neck cortex against this type of failure but not against crushing. We quantified the effect of aging on trabecular BMD in the femoral neck and assessed its contribution to cortical elastic stability, which determines resistance to buckling. Using CT, we measured ex vivo the distribution of bone in the midfemoral necks of 35 female and 33 male proximal femurs from cases of sudden death in those 20-95 yr of age. We calculated the critical stress sigma(cr), at which the cortex was predicted to buckle locally, from the geometric properties and density of the cortical zone most highly loaded in a sideways fall. Using long-established engineering principles, we estimated the amount by which stability or buckling resistance was increased by the trabecular bone supporting the most stressed cortical sector in each femoral neck. We repeated these measurements and calculations in an age- and sex-matched series of femoral necks donated by women who had suffered intracapsular hip fracture and controls, using histological measurements of cortical thickness to improve accuracy. With normal aging, trabecular BMD declined asymmetrically, fastest in the supero-lateral one-half (in antero-posterior projection) of the trabecular compartment. When viewed axially with respect to the femoral neck, the most rapid loss of trabecular bone occurred in the posterior part of this region (supero-posterior [S-P]), amounting to a 42% reduction in women (34% in men) over five decades of adult age. Because local cortical bone thickness declined comparably, age had no significant effect on the relative contributions of cortical and trabecular bone to elastic stability, and trabecular bone was calculated to contribute 40% (in men) and 43% (in women) to the S-P cortex of its overall elastic stability. Hip fracture cases had reduced elastic stability compared with age-matched controls, with a median reduction of 49% or 37%, depending on whether thickness was measured histologically or by CT (pQCT; p < 0.002 for both). This effect was because of reduced cortical thickness and density. Trabecular BMD was similar in hip fracture cases and controls. The capacity of the femur to resist fracture in a sideways fall becomes compromised with normal aging because cortical thickness and trabecular BMD in the most compressed part of the femoral neck both decline substantially. This decline is relatively more rapid than that of femoral neck areal BMD. If elastic instability rather than cortical crushing initiates the fracture event, interventions that increase trabecular bone in the proximal femur have great potential to reduce fracture risk because the gradient defining the increase in elastic stability with increasing trabecular BMD is steep, and most hip fracture cases have sufficient trabecular bone for anabolic therapies to build on.